2020
DOI: 10.1080/09602011.2020.1826331
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of a telehealth platform for delivering the Making Sense of Brain Tumour programme: A mixed-methods pilot study

Abstract: Glioma is a common type of brain tumour that is associated with neurocognitive and psychosocial impairments. This study primarily aimed to investigate the feasibility and acceptability of a videoconferencing format of the Making Sense of Brain Tumour (Tele-MAST) programme. Recruited from a multidisciplinary brain tumour clinic, participants were randomly allocated to the 10-session Tele-MAST programme or standard care, with the latter group offered Tele-MAST after reassessment. Semi-structured interviews explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…eHealth technology was valued for its role in helping users learn about the cancer experience. Participants with cancer found that information provided through eHealth echoed the advice of their healthcare team and standard care, which helped them understand the language around cancer or address their knowledge gaps regarding information they did not initially understand, potentially due to feeling overwhelmed (Brennan et al, 2020;Gustavell et al, 2020;Hauffman et al, 2020;Ownsworth et al, 2020;Ure et al, 2020). A number of studies highlighted that eHealth enabled people with cancer and family caregivers to prepare for hospital visits, navigate the healthcare system and engage more efficiently with the clinical team (Hauffman et al, 2020;Mohsen et al, 2021;Song et al, 2015).…”
Section: Understanding Of Cancer and Its Carementioning
confidence: 99%
See 4 more Smart Citations
“…eHealth technology was valued for its role in helping users learn about the cancer experience. Participants with cancer found that information provided through eHealth echoed the advice of their healthcare team and standard care, which helped them understand the language around cancer or address their knowledge gaps regarding information they did not initially understand, potentially due to feeling overwhelmed (Brennan et al, 2020;Gustavell et al, 2020;Hauffman et al, 2020;Ownsworth et al, 2020;Ure et al, 2020). A number of studies highlighted that eHealth enabled people with cancer and family caregivers to prepare for hospital visits, navigate the healthcare system and engage more efficiently with the clinical team (Hauffman et al, 2020;Mohsen et al, 2021;Song et al, 2015).…”
Section: Understanding Of Cancer and Its Carementioning
confidence: 99%
“…A number of studies highlighted that eHealth enabled people with cancer and family caregivers to prepare for hospital visits, navigate the healthcare system and engage more efficiently with the clinical team (Hauffman et al, 2020;Mohsen et al, 2021;Song et al, 2015). Additionally, two studies (Fang et al, 2020;Ownsworth et al, 2020) found that people with cancer mentioned completing the web-based psychoeducational platform intended for their use with their family caregiver, which in turn, they believed helped their relative to understand their condition. This parallels with Fergus and colleagues' (2014) finding that one third of male partners took part in the eHealth study to improve their understanding of their partner's breast cancer experience.…”
Section: Understanding Of Cancer and Its Carementioning
confidence: 99%
See 3 more Smart Citations